2014
DOI: 10.1124/jpet.114.216317
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanism of Intestinal Levodopa Absorption and Its Possible Implications for the Treatment of Parkinson’s Disease

Abstract: Levodopa (L-DOPA) is the naturally occurring precursor amino acid for dopamine and the main therapeutic agent for neurologic disorders due to dopamine depletion, such as Parkinson's disease. L-DOPA absorption in small intestine has been suggested to be mediated by the large neutral amino acids transport machinery, but the identity of the involved transporters is unknown. Clinically, coadministration of L-DOPA and dietary amino acids is avoided to decrease competition for transport in intestine and at the blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 59 publications
2
67
0
Order By: Relevance
“…Levodopa is used in the management of Parkinson's disease. Its absorption from the small intestine is mediated through an unknown large neutral amino acids transport pump (Carmago et al, 2014). The coadministration of Levodopa with dietary amino acids causes an increase in the competition for transport in the small intestine and at the blood-brain barrier, thus decreasing the bioavailability of Levodopa (Carmago et.…”
Section: Discussionmentioning
confidence: 99%
“…Levodopa is used in the management of Parkinson's disease. Its absorption from the small intestine is mediated through an unknown large neutral amino acids transport pump (Carmago et al, 2014). The coadministration of Levodopa with dietary amino acids causes an increase in the competition for transport in the small intestine and at the blood-brain barrier, thus decreasing the bioavailability of Levodopa (Carmago et.…”
Section: Discussionmentioning
confidence: 99%
“…9 The latter finding provides opportunities for augmenting dietary intervention. Serine supplementation increased in silico the bioavailability of levodopa for PD patients with moderately impaired GER (Figure 3d).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that, in addition to luminal competition, the presence of amino acids in the basolateral side of enterocytes trans-stimulates the absorption of levodopa leading to a higher bioavailability of the drug. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Some AA, peptide, and other SLC transporters have been shown to carry a broad variety of drugs (e.g., levodopa, antibiotics, ACE inhibitors etc)45. Thus, our approach could potentially be helpful in modeling SLC transporter responses to drugs even when the protein expression of candidate transporters is not known.…”
Section: Discussionmentioning
confidence: 99%